Scalar-Torsion Dynamics in Unified Cosmogenesis: The Foundation of Nudimmud Physics - Derrick Covington (New Horizons of Science, Technology and Culture Vol. 1, 2025)
Background: The reconciliation of quantum mechanics with gravitational theory remains one of the most significant challenges in contemporary physics. General Relativity and Quantum Field Theory have separately offered profound insights into the nature of the universe, yet attempts at unification frequently encounter conceptual and mathematical obstacles, notably the emergence of singularities and inconsistencies at extreme energy scales. Aims: To develop a unified scalar-torsion cosmological framework—Nudimmud Physics—that resolves quantum gravity and cosmological singularities, and to validate its predictive capability through explicit comparison with established cosmological models and observational data. Methodology: Theoretical and computational comparative study was conducted at the Department of Theoretical Physics and Computational Cosmology at GreenTheDream.com, from March 2024 to March 2025. A simplified unified scalar potential derived from scalar-torsion cosmology, quantum gravity principles inspired by Loop Quantum Gravity, and scalar moduli stabilisation mechanisms from String Theory was constructed. Numerical simulations were conducted to explore cosmological dynamics across bounce scenarios, focusing on scalar potential behaviours, cosmological growth factors, and observable parameters such as matter clustering and Hubble expansion rates. Results: Simulations using the refined unified scalar potential V (a) = \(Φeff 1+αa^2\) e -\(β\)|a| demonstrated smooth cosmological bounce behavior, effectively resolving the cosmological singularity at a cosmic scale factor of zero. Predictive results indicated enhanced matter clustering with a clustering amplitude \(σ_8\) = 0.865 and an increased Hubble constant of HO = 70.55kms-1 Mpc-1 compared to standard cosmological observations (DESI data). The unified framework showed excellent alignment with both Loop Quantum Gravity and String Theory scalar moduli stabilisation. Nudimmud Physics successfully resolves fundamental cosmological and quantum gravity issues through a simplified, testable unified scalar-torsion model. It provides robust predictions that can be validated by contemporary cosmological surveys, potentially advancing the understanding of the universe dynamics and offering a simplified alternative for scalar field stabilisation in theoretical cosmology. The broader implications of this study are manifold. Nudimmud Physics simplifies the complex theoretical landscape traditionally associated with quantum gravity and cosmological research, providing an accessible yet powerful model for future investigations.